2023
DOI: 10.22521/edupij.2023.124.1
|View full text |Cite
|
Sign up to set email alerts
|

How Can ChatGPT Facilitate Teaching and Learning: Implications for Contemporary Education

Turgut Karakose,
Tijen Tülübaş

Abstract: Background/purpose -ChatGPT stands before educational professionals with all its benefits and pitfalls, urging them to maximize its benefits for all levels of education while consistently searching for ways to minimize its risks. In the same vein, it is gradually recognized as a promising tool to serve the needs of students in the contemporary and forthcoming society. To this end, the present paper seeks to accumulate the wealth of opportunities ChatGPT can offer for the benefit of learners and teachers while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Today, school leaders are expected to make digital leadership a significant part of school management practice and guide the efficient use of recent technologies for the benefit of teaching and learning (Karakose et al, 2022;Tülübaş et al, 2023). This attempt not only requires enabling a more digitally enhanced learning environment but also integrating these technologies to practice effective management and leadership in contemporary schools.…”
Section: Implications Of Ai For School Leadership and Managementmentioning
confidence: 99%
“…Today, school leaders are expected to make digital leadership a significant part of school management practice and guide the efficient use of recent technologies for the benefit of teaching and learning (Karakose et al, 2022;Tülübaş et al, 2023). This attempt not only requires enabling a more digitally enhanced learning environment but also integrating these technologies to practice effective management and leadership in contemporary schools.…”
Section: Implications Of Ai For School Leadership and Managementmentioning
confidence: 99%
“…Moreover, since November 2022, the rise of ChatGPT and other generative AI models has further amplified the significance of conducting a bibliometric study focusing on AI in teaching. As ChatGPT and similar models become increasingly prevalent in educational contexts [30,31] understanding the research landscape and the impact of AI in teaching becomes even more imperative. These powerful language models are characterized by the possibility to revolutionize educational practices by offering personalized tutoring, generating interactive learning content, and assisting teachers in designing more effective instructional materials [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In their rapidly changing environment, the goals and tasks of schools are rapidly changing. Hence, the competencies and efficacy of educational professionals have become even more important in training students as citizens of a future society [1][2][3]. Research has continuously shown that school leadership is vital in increasing the instructional capacity of schools for sustained improvement and effective learner outcomes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%